Pregled sodobne slovenske mladinske proze - Haramija, Dragica (Jezik in slovstvo, 2005)
A significant development of some literary text types and genres (such as the contemporary fairytale, fantasy narrative, tale, youth novel) can be observed when researching contemporary Slovene youth prose. What can also be noted is the employment of contemporary themes and motifs, a detailed portrayal of literary characters, and, with most writers, also an exceptional sense for language. The article presents a selection of authors and their works, written during the last decade with some earlier exceptions, if they had made a significant impact on the development of Slovene youth prose. The works were selected according to their quality, interesting literary type, and topical themes and motifs. Also foregrounded in the opus of individual authors are those youth prose works, which particularly signify the authors and aid in their detailed presentation.
Keywords: mladinska književnost; pregledi; prose; proza; Slovene literature; slovenska književnost; slovenska mladinska književnost; young adult literature